2023
DOI: 10.1124/jpet.122.001455
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Pharmacokinetic and Pharmacodynamic Properties of the Antiarrhythmic Moleculeent-Verticilide

Abstract: The unnatural verticilide enantiomer (ent-verticilide) is a selective and potent inhibitor of cardiac ryanodine receptor (RyR2) calcium release channels and exhibits antiarrhythmic activity in a murine model of catecholaminergic polymorphic ventricular tachycardia (CPVT). To determine verticilide's pharmacokinetic and pharmacodynamic properties in vivo, we developed a bioassay to measure nat-and ent-verticilide in murine plasma and correlated plasma concentrations with antiarrhythmic efficacy in a mouse model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 31 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…5B and (Batiste et al, 2019)). As reported for ent-1 (Blackwell et al, 2023), we also observe a clear dose-dependent effect of ent-B1 in vivo (Fig. 5).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…5B and (Batiste et al, 2019)). As reported for ent-1 (Blackwell et al, 2023), we also observe a clear dose-dependent effect of ent-B1 in vivo (Fig. 5).…”
Section: Discussionsupporting
confidence: 88%
“…ent-B1's combination of sub-micromolar potency and partial channel inhibition is ideal for our target, as a stronger inhibition of RyR2 could be fatal given its central role in physiologic excitation-contraction coupling. Although peak plasma concentration was comparable to ent-1, our pharmacokinetic study revealed a more rapid systemic clearance of ent-B1 (t 1/2 = 45 min, table 1) relative to ent-1 (415 min) in mice (Blackwell et al, 2023). Given the short half-life, ent-B1 would only be useful in acute clinical scenarios unless the drug formulation is modified to produce a sustainedrelease profile.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…All protocols and procedures were compliant with Animal care and Use Application approved by the Institution Animal Care and Use Committee of Pharmaron, Inc., following the guidance of the Association for Assessment and Accreditation of Laboratory Animal Care (AAALAC). Based on our previous study with ent-1 (Blackwell et al, 2023), an ent-B1 dose of 3 mg/kg (drug/body weight) was used. Three CD1 mice (all males) 6-8 weeks old were selected for the study.…”
Section: Methodsmentioning
confidence: 99%